Cryptocurrencies: An empirical view from a tax perspective - Andreas Thiemann (European Commission, Joint Research Centre (JRC), 2021)
This paper sheds light on the scarce empirical evidence on cryptocurrency users and use types. Based on the only available empirical estimate, shared by Chainalysis, this paper simulates the revenue potential from taxing Bitcoin capital gains in the EU. Total estimated Bitcoin capital gains in the EU amount to 12.7 billion EUR in 2020, including 3.6 billion EUR of realized gains. Applying national tax rules on capital gains from shares to those from Bitcoin yields a simulated tax revenue of about 850 million EUR in 2020. This paper is the first to empirically assess the tax revenue potential of capital gains from Bitcoin in the EU. While most of the empirical cryptocurrency literature is based on time-series data, this paper relies on dis-aggregated country-level data. The findings show that revenue from taxing cryptocurrencies is nonnegligible and will be if the market of cryptocurrencies continues to grow.
Keywords: G19; G23; H24; 330; Capital gains taxation; cryptocurrencies; Bitcoin